Institutionalizing Innovation: A Study of Organizational Learning SystemsInstitutionalizing Innovation: A Study of Organizational Learning Systems, by JelinekMariann. New York: Praeger Publishers, 1979, 197 pp., $19.95. - Schoonhoven, Claudia Bird (Academy of Management Review, 1982)
The article reviews the book ?Institutionalizing Innovation: A Study of Organizational Learning Systems,? by Mariann Jelinek.